2022
DOI: 10.3390/antibiotics11030375
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Ceftriaxone Compared to Standard of Care for Treatment of Bloodstream Infections Due to Methicillin-Susceptible Staphylococcus aureus: A Systematic Review and Meta-Analysis

Abstract: (1) Background: Ceftriaxone is a potential alternative for the treatment of methicillin-susceptible Staphylococcus aureus (MSSA) bloodstream infections (BSIs) in acute care and outpatient parenteral antimicrobial therapy (OPAT) settings. We evaluated the effectiveness and safety of ceftriaxone for the treatment of MSSA BSIs. (2) Method: We searched PubMed, Embase, and Cochrane Library from their inception to October 30th 2021. Our outcomes included clinical cure, microbiological cure, 30- and 90-day mortality,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…A subgroup analysis of IE treated with ceftriaxone ( n = 42) compared to cefazolin or oxacillin ( n = 41) demonstrated ceftriaxone to be associated with a numerically higher rate of both the primary composite outcome (25.6% vs. 10%, p = 0.17) and 90-day all-cause mortality (14.3% vs. 2.4%, p = 0.11) [ 23 ]. Most recently, a systematic review and meta-analysis evaluated the use of ceftriaxone ( n = 1037) compared to standard of care (SOC) ( n = 2088) therapies (i.e., ASPs and cefazolin) in MSSA bacteremia [ 24 ]. It did not identify a statistically significant difference between groups for clinical cure, microbiologic cure, 30-day/90-day mortality, 90-day hospital readmission, or adverse drug reaction (ADR) occurrence.…”
Section: Beta-lactam Selection In Methicillin-susceptible S...mentioning
confidence: 99%
See 1 more Smart Citation
“…A subgroup analysis of IE treated with ceftriaxone ( n = 42) compared to cefazolin or oxacillin ( n = 41) demonstrated ceftriaxone to be associated with a numerically higher rate of both the primary composite outcome (25.6% vs. 10%, p = 0.17) and 90-day all-cause mortality (14.3% vs. 2.4%, p = 0.11) [ 23 ]. Most recently, a systematic review and meta-analysis evaluated the use of ceftriaxone ( n = 1037) compared to standard of care (SOC) ( n = 2088) therapies (i.e., ASPs and cefazolin) in MSSA bacteremia [ 24 ]. It did not identify a statistically significant difference between groups for clinical cure, microbiologic cure, 30-day/90-day mortality, 90-day hospital readmission, or adverse drug reaction (ADR) occurrence.…”
Section: Beta-lactam Selection In Methicillin-susceptible S...mentioning
confidence: 99%
“…Only 7 of the 12 studies included enrolled patients with IE (11.5% of total cohort with IE), and the treatment distribution was routinely skewed toward the SOC arm. As a result, the authors concluded that the findings could not be extrapolated to IE given the underrepresentation in the population [ 24 ].…”
Section: Beta-lactam Selection In Methicillin-susceptible S...mentioning
confidence: 99%
“…Ceftriaxone is one of the commonly utilized antibiotics due to its commendable antibacterial efficacy and excellent activity against many Gram-negative and most Gram-positive bacteria in patients with bacteremia, pneumonia, a urinary tract infection, necrotizing soft tissue infection, bone and joint infections, and bacterial meningitis [ 29 , 30 , 31 , 32 , 33 ]. Although the increasing prevalence of ceftriaxone-resistant Gram-negative pathogens has been reported as a concerning issue in critically ill patients, ceftriaxone is still recommended to be effective for blood stream infections and various community-acquired infections due to its excellent safety profile in many literatures [ 24 , 25 , 26 , 34 , 35 , 36 , 37 ]. Our study demonstrated that 89.2% of Gram-positive and Gram-negative pathogens was susceptible to ceftriaxone.…”
Section: Discussionmentioning
confidence: 99%
“…Previous cohort studies of patients with MS-SAB had highlighted worse outcomes with ceftriaxone when compared with cefazolin and/or cloxacillin [29,30]. Two meta-analyses were recently reported [31,32], and concluded to similar mortality outcomes when comparing ceftriaxone with SOC for MS-SAB or MSSA infections. All included studies were retrospective observational, which carries a high risk of bias by indication and residual confounding.…”
Section: Antibiotic Choicementioning
confidence: 99%